PMBOK® and critical chain practices: Antagonisms and opportunities for complementation - Luiz, João Victor Rojas [UNESP]; De Souza, Fernando Bernardi [UNESP]; Luiz, Octaviano Rojas [UNESP] (FapUNIFESP (SciELO), 2017)
The endeavor of the Project Management Institute (PMI) in gathering and codifying valuable knowledge in the field of Project Management (PM) has resulted in A Guide to the Project Management Body of Knowledge (PMBOK® Guide). Goldratt has contributed to the body of knowledge in PM to develop the Critical Chain Project Management (CCPM) method, based on the Theory of Constraints (TOC). CCPM superficially recommended by the PMBOK® Guide introduces new concepts and methods aimed at PM, some of which conflict with the practices recommended by the guide itself. This research assumes that CCPM can bring significant benefits to the field of knowledge in PM and questions the little relevance given to it in the PMBOK® Guide. Therefore, the general proposal of the study is initially checking the degree of insertion of CCPM in the Guide, and then evaluating possible contradictions as well as opportunities for complementation between them. The analysis was based on a literature review and a field study with certified experts. Despite the fact that CCPM is recommended by the Guide as a method aimed at Time Management, the research indicated that other practices involving CCPM and not covered by the Guide can contribute not only to Time Management, but also to Human Resources and Communications. The research also found that CCPM is not self-sufficient in its practices, and the Guide should be referred to especially on Integration and Scope Management. It was further noted that CCPM conflicts with certain time-management practices recommended by the Guide that, if used concurrently, may potentially jeopardize the effectiveness of PM.
Keywords: Critical chain; Guide; PMBOK®; Projects management